COVID-19 and expatriate faculty at an international university in Kazakhstan (Comparative & International Education Series, 2021)
This chapter summarizes the results of an empirical study investigating the experiences of expatriate faculty at an international university in Kazakhstan. COVID-19 presented a number of challenges for expatriate faculty at the university in terms of teaching, research, and service. Many of these challenges were similar to challenges of the domestic and international faculty employed at established universities in Western contexts. Expatriate faculty also faced some unique challenges in their work determined by the characteristics of their students, the nature of the university, and their location outside their home country. These unique challenges created additional psychological stress and load, which should be taken into consideration and properly addressed by the administration of international universities to maintain the faculty’s organizational commitment and the ability to deliver high quality of teaching, research and service.